Legal Protection for Workers on Termination of Employment That Occurs Due to Force Majeure According to the Law - Labor Copyright Law - Souki Aditya Pratama Kesdu; Erikson Sihotang; I Nyoman Suandika (Jurnal Syntax Transformation, 2024)
Labor has an imperative part as one of the supporting components in improvement. Making strides human quality cannot be accomplished without a certain ensure of life to be gotten, and moving forward the quality of labor and assurance of labor must be balanced to human respect. This consider points to analyze the Covid-19 widespread as a circumstance that qualifies as constrain majeure concurring to the Labor Law, and to look at the lawful results of end of work carried out on the grounds of drive majeure due to the Covid-19 widespread. The investigate strategy utilized is standardizing investigate strategy backed by observational investigate utilizing different sorts of essential lawful materials within the frame of laws and controls and secondary legitimate materials within the frame of literature related to legitimate security for specialists within the occasion of end of work due to drive majeure. The comes about appear that the Covid-19 widespread can be qualified as a drive majeure beneath the Labor Law, and end of work carried out on the grounds of constrain majeure due to the Covid-19 widespread has legitimate results within the frame of employers' commitments.